Characterization of a novel thermophilic phospholipase B from Thermotoga lettingae TMO: applicability in enzymatic degumming of vegetable oils. (1st April 2015) - Wei, Tao; Xu, Chunping; Yu, Xuan; Jia, Weiwei; Yang, Kunpeng; Jia, Chunxiao; Mao, Duobin
Abstract: A novel phospholipase B (TLPLB) from Thermotoga lettingae TMO has been cloned, functionally overexpressed in Escherichia coli and purified to homogeneity. Gas chromatography indicated that the enzyme could efficiently hydrolyze both the sn -1 and sn -2 ester bonds of 1-palmitoyl-2-oleoyl phosphatidylcholine as phospholipase B. TLPLB was optimally active at 70 °C and pH 5.5, respectively. Its thermostability is relatively high with a half-life of 240 min at 90 °C. TLPLB also displayed remarkable organic solvent tolerance and maintained approximately 91–161 % of its initial activity in 20 and 50 % (v/v) hydrophobic organic solvents after incubation for 168 h. Furthermore, TLPLB exhibited high degumming activity towards rapeseed, soybean, peanut and sunflower seed oils, where the phosphorus contents were decreased from 225.2, 189.3, 85.6 and 70.4 mg/kg to 4.9, 4.7, 3.2 and 2.2 mg/kg within 5 h, respectively. TLPLB could therefore be used for the degumming of vegetable oils.